Factors Associated with the Social and Environmental Reporting of Australian Companies - Asit Bhattacharyya (Australasian Accounting, Business and Finance Journal, 2014)
Purpose: The objective of this study is twofold. Firstly, to examine the extent of social and environmental reporting in Australia, selected Global Reporting Initiative (GRI, 2002) social and environmental reporting guidelines were used to determine the extent; secondly, to analyse the association between firm characteristics and Levels of Social and Environmental reporting (SER), regression analysis was used to test the hypotheses. Design/methodology/approach: This study investigated SER practices of 47 small and large Australian companies drawn from five industries. Using seventeen social and eighteen environmental disclosure indicators, the study evaluates disclosure information presented in annual reports. Regression analysis was used to empirically examine the determinants of SER. Findings: The results indicated that the extent of SER by Australian Companies was fairly low and the extent of total disclosure was significantly higher for large organisations in the Industrial Transport industry. Companies with negative return on total assets reported significantly higher social information. The extent of total disclosure was unrelated to an organisation’s age and external auditor size. Originality/value: The study provided a detailed analysis of the SER from the developing economy perspective using GRI social and environmental performance indicators. Research limitations/implications: The study was limited by the use of selected GRI social and environmental indicators. Practical and Social implications: The paper argues for greater social and environmental accounting researcher engagement with SEA practice. The study showed the gap and challenge still lies ahead in improving the quantity and quality of SEA from a developed economy perspective.
Keywords: Social reporting; environmental reporting; Global Reporting Initiative (GRI); Social and environmental reporting (SER)